Effect of Allylic Groups on SN2 Reactivity - Erden, Ihsan; Gronert, Scott; Keeffe, James R.; Ma, Jingxiang; Ocal, Nuket; Gaertner, Christian; Soukup, Leah L. (AMER CHEMICAL SOC, 2014)
The activating effects of the benzyl and allyl groups on S(N)2 reactivity are well-known. 6-Chloromethyl-6-methylfulvene, also a primary, allylic halide, reacts 30 times faster with KI/acetone than does benzyl chloride at room temperature. The latter result, as well as new experimental observations, suggests that the fulvenyl group is a particularly activating allylic group in S(N)2 reactions. Computational work on identity S(N)2 reactions, e.g., chloride-displacing chloride and ammonia displacing ammonia, shows that negatively charged S(N)2 transition states (tss) are activated by allylic groups according to the Galabov-Allen-Wu electrostatic model but with the fulvenyl group especially effective at helping to delocalize negative charge due to some cyclopentadienide character in the transition state (ts). In contrast, the triafulvenyl group is deactivating. However, the positively charged S(N)2 transition states of the ammonia reactions are dramatically stabilized by the triafulvenyl group, which directly conjugates with a reaction center having S(N)1 character in the ts. Experiments and calculations on the acidities of a variety of allylic alcohols and carboxylic acids support the special nature of the fulvenyl group in stabilizing nearby negative charge and highlight the ability of fulvene species to dramatically alter the energetics of processes even in the absence of direct conjugation.
Keywords: ALLENE OXIDE; NUCLEOPHILIC-SUBSTITUTION; INORGANIC IODIDES; ORGANIC HALIDES; SINGLET OXYGEN; FULVENE; CHEMISTRY; MECHANISM; RESONANCE